Fetal lower urinary tract obstruction: proposal for standardized multidisciplinary prenatal management based on disease severity. (October 2016) - Ruano, R.; Sananes, N.; Wilson, C.; Au, J.; Koh, C. J.; Gargollo, P.; Shamshirsaz, A. A.; Espinoza, J.; Safdar, A.; Moaddab, A.; Meyer, N.; Cass, D. L.; et al.
ABSTRACT: Objective: To present a single center experience of a standardized prenatal multidisciplinary management protocol for fetal lower urinary tract obstruction (LUTO) and to propose a classification of fetal LUTO based on disease severity. Methods: This was a retrospective cohort study of 25 consecutive fetal patients with prenatal diagnosis of primary LUTO. Fetal intervention was offered after evaluation by a multidisciplinary team. Analyses were conducted using Bayesian methodology to determine predictors of survival at 6 months postpartum. Odds ratios (ORs) with 95% credibility intervals are reported. Results: Fifteen (60.0%) of the 25 patients referred for assessment survived to postnatal evaluation. Fetal vesicoamniotic shunt was placed in 14 (56.0%) patients with 12 survivors. Multivariable analysis suggested that fetal intervention (OR, 6.97 (0.88–70.16), Pr(OR > 1) = 96.7%), anhydramnios (OR, 0.12 (0.04–0.35), Pr(OR < 1) = 99.9%), favorable fetal urine analysis (OR, 3.98 (0.63–25.15), Pr(OR > 1) = 92.7%) and absence of renal cortical cysts (OR, 3.9 (0.66–24.2), Pr(OR > 1) = 93.3%) were predictors of survival. Conclusions: Fetal intervention and fetal renal function were independently associated with postnatal survival of fetuses with LUTO. A classification based on the severity of disease is proposed. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.